Identification of a Novel OFD1 Variant in a Patient with Primary Ciliary Dyskinesia - Yang B; Lei C; Yang D; Lu C; Xu Y; Wang L; Guo T; Wang R; Luo H (Dove Medical Press, 2022)
Binyi Yang,1– 3,* Cheng Lei,1– 3,* Danhui Yang,1– 3 Chenyang Lu,1– 3 Yingjie Xu,1– 3 Lin Wang,1– 3 Ting Guo,1– 3 Rongchun Wang,1– 3 Hong Luo1– 3 1Department of Pulmonary and Critical Care Medicine, The Second Xiangya Hospital, Central South University, Changsha, Hunan, 410011, People’s Republic of China; 2Research Unit of Respiratory Disease, The Second Xiangya Hospital, Central South University, Changsha, Hunan, 410011, People’s Republic of China; 3Hunan Diagnosis and Treatment Center of Respiratory Disease, The Second Xiangya Hospital, Central South University, Changsha, Hunan, 410011, People’s Republic of China*These authors contributed equally to this workCorrespondence: Rongchun Wang; Hong Luo, Department of Pulmonary and Critical Care Medicine, The Second Xiangya Hospital, Central South University, Changsha, Hunan, 410011, People’s Republic of China, Email 198202060@csu.edu.cn; luohonghuxi@csu.edu.cnBackground: OFD1 encodes a protein with 1012 amino acids, which is a component of basal bodies and centrioles, essential for cilia biogenesis. OFD1 was reported to be associated with X-chromosome linked dysmorphology syndrome in early studies and recent studies reported a few cases with primary ciliary dyskinesia (PCD) caused by OFD1 deficiency.Case Presentation: We report a 31-year-old man who suffered from recurrent respiratory infections with typical manifestations of primary ciliary dyskinesia. In addition to respiratory manifestations, the patient also had situs inversus, obesity, gastroesophageal reflux, and hearing impairment. Clubbing fingers and mild streblomicrodactyly were also observed.Examination Result: We performed whole-exome sequencing to identify a novel variant c.2795delA:p.(Lys932Argfs*3) in OFD1. The hemizygous variant was predicted to be likely pathogenic by bioinformatic analysis software and ACMG guideline. High-speed video microscopy (HSVM), transmission electron microscopy (TEM), and immunofluorescence were performed to analyze the respiratory cilia. A high beating frequency and a stiff beating pattern were observed under HSVM, while there were no significant abnormalities in TEM and immunofluorescence. The sperm flagella examinations were also generally normal.Conclusion: Our study identified a novel frameshift variant in OFD1 causing PCD, enriched the genetic spectrum of OFD1 variants, and verified that OFD1 mutation can lead to only a PCD characteristic phenotype, while other OFD1-associated syndromic symptoms such as dysmorphic features and renal symptoms were not present.Keywords: OFD1, primary ciliary dyskinesia, cilia, situs inversus